2006
DOI: 10.1631/jzus.2006.b0142
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of mitochondria responsible for the anti-apoptotic effects of melatonin during ischemia-reperfusion

Abstract: Abstract:Objective: To investigate a possible mechanism responsible for anti-apoptotic effects of melatonin and provide theoretical evidences for clinical therapy. Methods: Ischemia-reperfusion mediated neuronal cell injury model was constructed in cerebellar granule neurons (CGNs) by deprivation of glucose, serum and oxygen in media. After ischemia, melatonin was added to the test groups to reach differential concentration during reperfusion. DNA fragmentation, mitochondrial transmembrane potential, mitochond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…After matrine application, the mitochondrial-free cytosolic fraction and solubilized mitochondrial fraction were extracted from myeloma cells according to our previous study [13], and were then subjected to quantitation by employing a bicinchoninic acid protein concentration assay kit (Beyotime, Jiangsu, China). Cyt c protein was measured with a commercially available cyt c enzyme-linked immunosorbent assay (ELISA) kit (Calbiochem, San Diego, CA, USA) according to the manufacturer's instructions.…”
Section: Cyt C Assaymentioning
confidence: 99%
“…After matrine application, the mitochondrial-free cytosolic fraction and solubilized mitochondrial fraction were extracted from myeloma cells according to our previous study [13], and were then subjected to quantitation by employing a bicinchoninic acid protein concentration assay kit (Beyotime, Jiangsu, China). Cyt c protein was measured with a commercially available cyt c enzyme-linked immunosorbent assay (ELISA) kit (Calbiochem, San Diego, CA, USA) according to the manufacturer's instructions.…”
Section: Cyt C Assaymentioning
confidence: 99%
“…One of those small molecules that can be released is the cytochrome c [Krysko et al, 2001]. Cytosolic cytochrome c reacts with other proteins and activates pro‐caspase 3 triggering apoptosis [Han et al, 2006]. Insulin, which is present in HBS, is known to exert protection against I/R injury by inhibiting intracellular calcium transients [Yu et al, 2008], which may explain the overall higher protection against mitochondrial‐mediated apoptotic signaling in HBS‐preserved hearts.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, melatonin reperfusion of ischemic hearts significantly lowered the degree of mitochondrial lipid peroxidation, prevented the loss in ETC function and the increase of H 2 O 2 production (Petrosillo et al, 2006), inhibited the formation of mPTP and related events, and preserved the content and integrity of CL molecules, suggesting a possible link between these processes (Petrosillo et al, 2009;Paradies et al, 2010). Focusing on the apoptotic pathway, it has been observed that the indole inhibits cytochrome C release and caspase 1 and 3 activation, thus preventing DNA fragmentation (Andrabi et al, 2004;Han et al, 2006;Wang et al, 2009). In other words, scientific evidence indicates that melatonin's effect during I/R is not only due to its direct/indirect antioxidant properties, but also due to its influence over mitochondrial homeostasis and dynamics (Srinivasan et al, 2010;Huang et al, 2013).…”
Section: Ischemia/reperfusion Challenge In Organ Transplantation and mentioning
confidence: 98%
“…Similarly, most cerebral ischemia induced by various factors can be transiently reversed, although reperfusion produces further neuron damage (Han et al, 2006). After I/R, the oxidative stress, derived from impairment of ETC function (C-I and C-III) among other sources, is worsened by the concomitant depletion of endogenous antioxidants.…”
Section: Ischemia/reperfusion Challenge In Organ Transplantation and mentioning
confidence: 99%